2012
DOI: 10.4236/abb.2012.38134
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium induces liver toxicity through reductive activation by glutathione and mitochondrial dysfunction

Abstract: Pentavalent vanadium (V 5+) (metavanadate salt) toxicity is a challenging problem to the health professionals and has been recognized as an industrial hazard that adversely affects human and animal health, but its cytotoxic mechanisms have not yet been completely understood. In this study, we investigated the cytotoxic mechanisms of V 5+ in freshly isolated rat hepatocytes. V 5+ cytotoxicity was associated with reactive oxygen species (ROS) formation, collapse of mitochondrial membrane potential, lysosomal mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Moreover, the increase in green coloration (JC‐1 monomers) in the merged images indicates that the △ψm depolarization was severe, implying that early apoptosis was occurring, supporting our apoptosis results. A similar study reported that V induced the depolarization of △ψm in hepatic cells . Although P38 and ERK1/2 inhibitors reduced V‐induced depolarization of △ψm , the JNK inhibitor did not have this effect.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, the increase in green coloration (JC‐1 monomers) in the merged images indicates that the △ψm depolarization was severe, implying that early apoptosis was occurring, supporting our apoptosis results. A similar study reported that V induced the depolarization of △ψm in hepatic cells . Although P38 and ERK1/2 inhibitors reduced V‐induced depolarization of △ψm , the JNK inhibitor did not have this effect.…”
Section: Discussionmentioning
confidence: 62%
“…A similar study reported that V induced the depolarization of 5ψm in hepatic cells. 32 Although P38 and ERK1/2 inhibitors reduced V-induced depolarization of 5ψm, the JNK inhibitor did not have this effect. It could be argued that while P38 and ERK1/2 participate in the mitochondrial pathway that regulate apoptosis in OMECs exposed to V, JNK mediates are involved through another pathway.…”
Section: Discussionmentioning
confidence: 94%
“…Vanadium toxicity have been previously reported to induce anorexia [19] leading to the reduction in daily body weights which becomes significant following chronic exposure as reported by S á n c h e z et al [38] and T o d o r i c h et al…”
Section: Discussionmentioning
confidence: 88%
“…7). It has been suggested that the hepatotoxic, nephrotoxic [48,62,[68][69][70][71], cardiotoxic [72], genotoxic [73,74], neurotoxic [72,75,76], and carcinogenic [48,77] effects of this metal as well as inflammatory and fibrotic changes in the lungs [78] are associated with the pro-oxidative potential of V and its ability to intensify LPO ( Fig. 7).…”
Section: <Figure 7>mentioning
confidence: 99%